FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KAPASITA PARU PADA PEKERJA BATU BATA DI DESA TALANG BELIDO TAHUN 2022 - Nazira Nazira; Cici Wuni; Parman Parman (Jurnal Cakrawala Ilmiah, 2022)
Brick making is one of the informal home industries that has the potential for exposure to quite a lot of dust. At the time of initial observation of 10 workers, it was found that 70% of workers complained of shortness of breath. 70% of workers do not use masks when working, even though a workplace full of dust has the potential to cause respiratory problems for workers. The purpose of the study was to determine factors related to lung capacity in brick workers in Talang Belido Village. The research design used a cross sectional design. The research sample was 38 brick workers in Talang Belido Village. The sampling technique used was total sampling technique. This research was conducted in June 2022 in Talang Belido Village. The research instrument is a questionnaire. Data collection techniques by means of interviews and observations. Data were analyzed by univariate and bivariate using chi square test. A total of 15.8% of respondents have heavy lung capacity, 55.3% of respondents have moderate lung capacity, 52.6% of respondents work with risky dust levels, 71.1% of respondents have a long working period, 68.4% of respondents have a smoking habit. , 47.4% of respondents do not use masks. Bivariate results showed that there was a relationship between dust levels (p=0.034), smoking habits (p=0.021), use of masks (p=0.001) and lung capacity in brick workers in Talang Belido Village. There is no relationship between length of service (0.692) and lung capacity of brick workers in Talang Belido Village.